1989
DOI: 10.1159/000185722
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Neopterin as a New Biochemical Marker for the Monitoring of Disease Activity and Prognosis in Membranous Nephropathy Associated with Hepatitis B Surface Antigenemia

Abstract: In an attempt to find a parameter for the differentiation of membranous nephropathy with hepatitis B surface antigenemia (HBVMN) and other types of nephrotic syndrome (NS) in HBsAg (+) carriers, we measured the urinary neopterin in 20 HBVMN patients, other types of NS in HBsAg ( + ) carriers, asymptomatic HBsAg ( + ) carriers and HBsAg (-) controls, during the active nephrotic phase and in remission. The urinary neopterin excretion was found to be significantly elevated only in the HBVMN during NS or heavy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…These include: various immune-mediated clinical conditions, including transplantation rejection (11); hepatitis and other viral infections, such as human immunodeficiency virus and cytomegalovirus; bacterial infections (3,12, 13); autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis; tumors, such as hepatocellular carcinoma, stomach cancer, or uroepithelial cancer (14,15); congestive heart failure; renal failure; coronary artery disease; and, myocardial infarction. Weiss et al reported that neopterin is a marker for disease progression and complication in diabetes mellitus, such as glycation end-product pentosidine, and other inflammatory molecules, such as interleukin-6 and C-reactive protein (CRP) are (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include: various immune-mediated clinical conditions, including transplantation rejection (11); hepatitis and other viral infections, such as human immunodeficiency virus and cytomegalovirus; bacterial infections (3,12, 13); autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis; tumors, such as hepatocellular carcinoma, stomach cancer, or uroepithelial cancer (14,15); congestive heart failure; renal failure; coronary artery disease; and, myocardial infarction. Weiss et al reported that neopterin is a marker for disease progression and complication in diabetes mellitus, such as glycation end-product pentosidine, and other inflammatory molecules, such as interleukin-6 and C-reactive protein (CRP) are (16).…”
Section: Discussionmentioning
confidence: 99%
“…Neopterin levels in body fluids are elevated in a variety of diseases in which T cells or macrophages are activated (1,2). Therefore, neopterin levels can be useful for the evaluation of disease activity and prognosis in a variety of conditions (3-7). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its levels are elevated in several conditions including autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis [4]; infections such as hepatitis, human immunodeficiency virus, and cytomegalovirus [57]; cancers like hepatocellular, gastric, and urothelial carcinomas [8, 9]; congestive heart failure; coronary artery disease and myocardial infarction and transplant rejection [1013]. Neopterin has been reported as a marker of disease progression and complication in diabetes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Neopterin has been reported to be a useful marker in detecting graft rejection and cytomegalovirus infection in kidney transplant recipients 3,19–29 . In contrast, the information about interrelation between neopterin and glomerulonephritis has been very limited 30–32 . Godai et al 10 reported that urinary neopterin was a valuable marker for the differential diagnosis of membranous nephropathy associated with hepatitis B surface antigenemia and yet to serve as a prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%